THU0341 Cost Effectiveness Analysis of Abatacept Compared with Adalimumab on Background Methotrexate in Biologic-Naïve RA Adult Patients by Anti-Cyclic Citrullinated Peptide-Positive Subgroups. (9th June 2015) - Alemao, E.; Schiff, M.; Johal, S.; Al, M.; Rutten-van Molken, M.
Abstract : Background: Antibodies to cyclic citrullinated peptide-2 (CCP-2) are highly specific to RA and a high level of CCP-2 is associated with radiographic progression and progression of disability in RA patients (pts). High-quartile CCP-2+ pts treated with abatacept (ABA) showed better DAS28 (CRP) and HAQ response vs pts treated with adalimumab (ADA) in the Abatacept versus Adalimumab Comparison in Biologic-Naïve RA Subjects with Background Methotrexate (AMPLE) study. 1 Objectives: To evaluate costs and benefits of treating CCP-2+ RA pts with ABA compared with ADA, on background MTX. Methods: An economic model was developed that estimated lifetime HAQ progression, quality-adjusted life years (QALYs) and direct costs for RA pts treated with ABA or ADA, from a UK NHS perspective. QALYs are a measure of a life lived, adjusted to reflect quality of life. The population modelled reflected baseline characteristics of CCP-2+ pts by quartile (Q) from AMPLE. HAQ changes by CCP-2+ Q due to treatment were modelled based on responses to ABA and ADA in AMPLE. CCP-2+ Q were defined by dividing the range of CCP-2 values into 4 equal parts. Mean long-term survival on treatment with ABA or ADA was derived from AMPLE and published literature. 2 In the base case, pts discontinuing ABA or ADA moved to etanercept, followed by palliative care (conventional DMARDs). Direct medical costs and quality-of-life scores were correlated to HAQ score. 2 Costs included hospitalization, joint replacement and treatment. Estimates of differences in costs and QALYs between ADA and ABA were used to calculate an incremental cost-effectiveness ratio (cost per QALY gained). A sensitivity analysis examined the effect of varying the input parameters of efficacy, cost and utilities on costs and benefits. Results: Based on the range of CCP-2 values there were no pts in Q4 and only a few pts in Q3 (n=7). Hence, only Q1 (n=316) and Q2 (n=63) pts were considered in this analysis. For Q1 pts, the total estimated QALYs for ABA and ADA were 5.53 and 5.07, respectively. Total lifetime costs were £122, 585 and £110, 670, respectively. For Q2 pts, the total estimated QALYs for ABA and ADA were 5.29 and 4.71, respectively; total lifetime costs were £126, 599 and £116, 299. The lifetime cost for ABA pts was higher compared with ADA pts in both CCP-2+ Qs owing to the longer duration of ABA therapy. The cost per QALY for ABA (vs ADA) in Q1 was £25, 941/QALY and in Q2 was £17, 907/QALY. An intervention with a cost per QALY gain of less than £30, 000 is generally considered to be cost effective in the UK. In a sensitivity analysis, in which mean long-term time on treatment was assumed to be the same for ABA and ADA (4.06 years), for Q2 pts, ABA achieved a QALY gain of 0.10 with an incremental cost of £211 (cost per QALY of £2110). Conclusions: Abatacept is projected to be a cost-effective alternative to adalimumab in CCP-2+ pts. The increased treatment costs of ABA were accompanied by a gain in benefits (QALYs) owing to higher HAQ reduction and lower hospitalization costs.The cost per QALY for abatacept (vs adalimumab) is lower in CCP-2+ pts with higher CCP-2 levels. References: Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Malottki K, et al. Health Technol Assess 2011;15:1–278. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Schiff Grant/research support from: UCB, Consultant for: AbbVie, Amgen, Antares, Bristol-Myers Squibb, Eli Lilly, Horizon, Johnson and Johnson, Novartis, Novo Nordisk, Pfizer, Roche, UCB, Speakers bureau: AbbVie, S. Johal Consultant for: Bristol-Myers Squibb, M. Al: None declared, M. Rutten-van Molken Grant/research support from: BMS has paid Erasmus University Rotterdam a grant to support the PhD thesis of Evo Alemao